Optimalisasi Kompetensi Pedagogi Guru MTs Assalaam Kota Kartasura melalui Inovasi Model Pembelajaran untuk Menguatkan Literasi Siswa - Ratna Dewi, Novi; Nor Amelia, Rizki; Aji, Septiko; Arifudin, Riza; Damayanti, Tiara; Anggita, Anggita (Jurnal Dharma Indonesia, 2025)
This community service activity was carried out in response to the low level of student literacy and the limited implementation of innovative learning models at Madrasah Tsanawiyah (MTs) Pondok Pesantren Modern Islam (PPMI) Assalaam. MTs PPMI Assalaam is a boarding Islamic educational institution that integrates the national and pesantren curricula to develop graduates who are religious, academically competent, and of strong character. Through a collaborative-participatory approach, this training and mentoring program was designed to enhance teachers’ pedagogical competencies, particularly in applying literacy-based learning models within the TPACK (Technological Pedagogical Content Knowledge) framework. The program was conducted in three stages (preparation, implementation, and evaluation), and involved 59 teachers as participants. The results showed a significant improvement in content mastery, particularly regarding deep learning principles, digital literacy, partnership focus, and critical reasoning (p<0.05). Final evaluations indicated that the training was well-received, with high participant satisfaction and effective methods for strengthening both competence and innovative teaching practices. This program has proven effective in addressing 21st-century literacy challenges within the modern pesantren context, while fostering an adaptive, collaborative, and Islamically-rooted learning ecosystem